2005
DOI: 10.1038/sj.bjc.6602595
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The Akt inhibitor KP372-1 suppresses Akt activity and cell proliferation and induces apoptosis in thyroid cancer cells

Abstract: The phosphatidylinositol 3 0 kinase (PI3K)/phosphatase and tensin homologue deleted on chromosome ten/Akt pathway, which is a critical regulator of cell proliferation and survival, is mutated or activated in a wide variety of cancers. Akt appears to be a key central node in this pathway and thus is an attractive target for targeted molecular therapy. We demonstrated that Akt is highly phosphorylated in thyroid cancer cell lines and human thyroid cancer specimens, and hypothesised that KP372-1, an Akt inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 18 publications
(19 reference statements)
1
62
1
2
Order By: Relevance
“…FTC cells invading the thyroid capsule or blood vessels, or metastasizing to other areas, have been characterized by activation of Akt in a nuclear pattern, suggesting an association between Akt activity and progression of tumors (54). Our laboratory has shown that the inhibition of Akt phosphorylation by a novel Akt inhibitor successfully suppressed cellular growth and induced apoptosis in thyroid cancer cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…FTC cells invading the thyroid capsule or blood vessels, or metastasizing to other areas, have been characterized by activation of Akt in a nuclear pattern, suggesting an association between Akt activity and progression of tumors (54). Our laboratory has shown that the inhibition of Akt phosphorylation by a novel Akt inhibitor successfully suppressed cellular growth and induced apoptosis in thyroid cancer cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…However, depending upon Akt phosphorylation status, the mode of apoptosis induction is different [144,145] . KP372-1, a triazinones derivative (Figure 3), inhibits proliferation and induces apoptosis in thyroid cancer, glioblastoma, squamous cell cancer, and acute myelogenous leukemia cell lines [146][147][148][149] . It is also a PDK1 and FLT3 inhibitor that causes the inhibition of PKB activation through Ser473 phosphorylation, as well as downstream target phosphorylation, which reflects the non-selective mode of action.…”
Section: Akt Inhibitorsmentioning
confidence: 99%
“…Moreover, Akt1 and Akt2 are dispensable for cell survival in isolated osteoclast precursors (24), possibly because of the redundant function from Akt3. Although several Akt inhibitors have been reported to induce apoptosis in cancer cells, these inhibitors may have additional targets other than Akt (25)(26)(27)). In the current study, we used an Akt3 siRNA to analyze apoptosis induction in Akt1 and Akt2 double knock-out MEF cells (MEF-Akt1,2-DKO).…”
mentioning
confidence: 99%